2014
DOI: 10.1103/physrevlett.112.257201
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Spectral Purity and Tuning Sensitivity in a Spin Transfer Vortex Nano-Oscillator

Abstract: We investigate the microwave characteristics of a spin transfer nano-oscillator (STNO) based on coupled vortices as a function of the perpendicular magnetic field H(⊥). Interestingly, we find that our vortex-based oscillator is quasi-isochronous independently of H(⊥) and for a dc current ranging between 18 and 25 mA. It means that the severe nonlinear broadening usually observed in STNOs can be suppressed on a broad range of bias. Still, the generation linewidth displays strong variations on H(⊥) (from 40 kHz … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
(47 reference statements)
1
40
0
4
Order By: Relevance
“…We note that a similar interaction of steady state and damped modes via their harmonics has been reported in Ref. 18 for vortex excitations.…”
Section: Ivb4 Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We note that a similar interaction of steady state and damped modes via their harmonics has been reported in Ref. 18 for vortex excitations.…”
Section: Ivb4 Discussionmentioning
confidence: 71%
“…However, important questions remain open and many features observed experimentally cannot be explained in the frame of this 'independent free layer' picture. Recent investigations have addressed the coupling between the different magnetic layers of an STO and demonstrated that it strongly impacts the excitations spectra [6][7][8][9][10][11][12][13][14][15][16][17][18] , and that it can be exploited in the interest of the device performances [7][8][9][10] .…”
mentioning
confidence: 99%
“…For I dc 10 mA, a narrow microwave emission peak corresponding to the spin transfer driven dynamics of the two coupled vortices is detected on the spectrum analyzer. At fixed I dc , the microwave characteristics of this auto-oscillation peak (frequency and linewidth) can be tuned by varying H [34]. In this study, all measurements are carried out at room temperature.…”
mentioning
confidence: 99%
“…The magnetization configuration of each NiFe layers is at remanence a magnetic vortex state. We previously demonstrated that the excitation by mutual spin transfer torque of coupled vortex modes inside the NiFe/Cu/NiFe trilayers is detected at zero applied magnetic field [7,15,16]. Interestingly, this excited coupled mode displays very narrow linewidth (~100 kHz) [7,15,16].…”
mentioning
confidence: 99%
“…Indeed, thanks to their large intrinsic coherence compared to other types of STNOs [7,15,16], we succeed to elucidate the strong correlation between the oscillator parameters and the locking process through a thorough experimental study combining time domain measurements and analytical developments. This allows understanding of the locking range characteristics [8,17,18] as well as the high phase coherence in the locked regime [19][20][21].…”
mentioning
confidence: 99%